Transfer of bacteriophage MS2 and fluorescein from N95 filtering facepiece respirators to hands: Measuring fomite potential - Brady, Tyler M. (J Occup Environ Hyg, 2017)
Contact transmission of pathogens from personal protective equipment is a concern within the healthcare industry. During public health emergency outbreaks, resources become constrained and the reuse of personal protective equipment, such as N95 filtering facepiece respirators, may be needed. This study was designed to characterize the transfer of bacteriophage MS2 and fluorescein between filtering facepiece respirators and the wearer’s hands during three simulated use scenarios. Filtering facepiece respirators were contaminated with MS2 and fluorescein in droplets or droplet nuclei. Thirteen test subjects performed filtering facepiece respirator use scenarios including improper doffing, proper doffing and reuse, and improper doffing and reuse. Fluorescein and MS2 contamination transfer were quantified. The average MS2 transfer from filtering facepiece respirators to the subjects’ hands ranged from 7.6–15.4% and 2.2–2.7% for droplet and droplet nuclei derived contamination, respectively. Handling filtering facepiece respirators contaminated with droplets resulted in higher levels of MS2 transfer compared to droplet nuclei for all use scenarios (p = 0.007). MS2 transfer from droplet contaminated filtering facepiece respirators during improper doffing and reuse was greater than transfer during improper doffing (p = 0.008) and proper doffing and reuse (p = 0.042). Droplet contamination resulted in higher levels of fluorescein transfer compared to droplet nuclei contaminated filtering facepiece respirators for all use scenarios (p = 0.009). Fluorescein transfer was greater for improper doffing and reuse (p = 0.007) from droplet contaminated masks compared to droplet nuclei contaminated filtering facepiece respirators and for improper doffing and reuse when compared improper doffing (p = 0.017) and proper doffing and reuse (p = 0.018) for droplet contaminated filtering facepiece respirators. For droplet nuclei contaminated filtering facepiece respirators, the difference in MS2 and fluorescein transfer did not reach statistical significance when comparing any of the use scenarios. The findings suggest that the results of fluorescein and MS2 transfer were consistent and highly correlated across the conditions of study. The data supports CDC recommendations for using proper doffing techniques and discarding filtering facepiece respirators that are directly contaminated with secretions from a cough or sneeze.